Erratum to: Activity and diffusivity of oxygen in the liquid dilute BixSb1-x solutions, J. Min. Metall. Sect. B-Metall. 54 (2) B (2018) 261-270. DOI:10.2298/JMMB180311014J - Jendrzejczyk-Handzlik, Dominika; Handzlik, Piotr; Fitzner, Krzysztof (Journal of Mining and Metallurgy, Section B: Metallurgy, 2021)
/